MSCs Therapy Reverse the Gut Microbiota in Hypoxia-Induced Pulmonary Hypertension Mice - Luo, Lingjie; Chen, Qinhua; Yang, Lei; Zhang, Zhenxia; Xu, Jihong; Gou, Deming (Frontiers in Physiology, 2021)
Mesenchymal stem cell (MSC) therapy is a promising therapeutic approach based on its strong effect on pulmonary hypertension (PH) in rats. However, the detailed mechanism of MSC therapy remains unknown. Alterations in the gut microbiota were found in both type 1 pulmonary arterial hypertension patients and hypoxia/SU5416- or monocrotaline (MCT)-induced PH rats. However, whether the therapeutic mechanism of MSCs is associated with the gut microbiota is poorly understood. Here, we found that gut microbiota homeostasis was disrupted in hypoxia-induced PH mice due to the increased Firmicutes-to-Bacteroidetes (F/B) ratio; enhanced abundances of harmful Marinifilaceae, Helicobacteraceae, and Lactobacillaceae; and decreased abundances of beneficial Bacteroidaceae, Prevotellaceae, Tannerellaceae, and Lachnospiraceae. Unexpectedly, reverses of the increase in disease-associated microbiota and decrease in anti-inflammatory and immunomodulatory functional microbiota were observed in the MSC-treated group. We also identified harmful Erysipelotrichaceae, Alphaproteobacteria, Christensenella timonensis, Coriobacteriales, and Rhodospirillales that may serve as gut microbiota biomarkers of hypoxia-induced PH mice. Micrococcaales, Nesterenkonia, Anaerotruncus, and Tyzzerella may serve as gut microbiota biomarkers of MSC-treated mice. In summary, MSC treatment suppresses hypoxia-induced pulmonary hypertension in mice, and alterated gut microbiota may play a role in the development and progression of PH. The mechanism of MSC therapy is associated with various metabolic pathways of the gut microbiota in hypoxia model PH mice.